Beryllium Stress-Induced Modifications in Antioxidant Machinery and Plant Ultrastructure in the Seedlings of Black and Yellow Seeded Oilseed Rape. (21st March 2018) - Ali, Skhawat; Jin, Rong; Gill, Rafaqat A.; Mwamba, Theodore M.; Zhang, Na; Hassan, Zaid ul; Islam, Faisal; Ali, Shafaqat; Zhou, Weijun
Abstract : Beryllium (Be) could be a threatening heavy metal pollutant in the agroecosystem that may severely affect the performance of crops. The present study was conducted to evaluate the toxic effects of Be (0, 100, 200, and 400 μ M) on physiological, ultrastructure, and biochemical attributes in hydroponically grown six-day-old seedlings of two cultivars of Brassica napus L., one tolerant (ZS 758, black seeded) and one sensitive (Zheda 622, yellow seeded). Higher Be concentrations reduced the plant growth, biomass production, chlorophyll contents, and the total soluble protein contents. A significant accumulation of ROS (H2 O2, OH − ) and MDA contents was observed in a dose-dependent manner. Antioxidant enzymatic activities including SOD, POD, GR, APX, and GSH (except CAT) were enhanced with the increase in Be concentrations in both cultivars. Relative transcript gene expression of above-mentioned antioxidant enzymes further confirmed the alterations induced by Be as depicted from higher involvement in the least susceptible cultivar ZS 758 as compared to Zheda 622. The electron microscopic study showed that higher level of Be (400 μ M) greatly damaged the leaf mesophyll and root tip cells. More damage was observed in cultivar Zheda 622 as compared to ZS 758. The damage in leaf mesophyll cells was highlighted as the disruption in cell wall, immature nucleus, damaged mitochondria, and chloroplast structures. In root tip cells, disruption in Golgi bodies and damage in cell wall were clearly noticed. As a whole, the present study confirmed that more inhibitory effects were recorded in yellow seeded Zheda 622 as compared to black seeded ZS 758 cultivar, which is regarded as more sensitive cultivar.